(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article explores the concept of linguistic personality and its manifestation within contemporary media communication. It delves into how individual language use and personal linguistic styles are shaped by and contribute to the evolving landscape of media platforms. Emphasis is placed on the interaction between personal identity, linguistic choices, and media influence. The study examines various dimensions of linguistic personality, including sociolects, idiolects, and the impact of digital communication on language evolution. Through a detailed analysis of social media, news media, and digital content creation, the article highlights the significance of linguistic personality in shaping public discourse and personal expression in the modern media environment